1981
DOI: 10.1002/1098-2337(1981)7:1<51::aid-ab2480070107>3.0.co;2-f
|View full text |Cite
|
Sign up to set email alerts
|

The neural pathways mediating quiet-biting attack behavior from the hypothalamus in the cat: A functional autoradiographic study

Abstract: Electrical stimulation of the region of the lateral hypothalamus produced a consistent form of quiet‐biting attack behavior in cats. In one series of experiments, cats, implanted with electrodes from which attack had been elicited, were anesthetized and then were injected with a bolus of 14C‐2‐deoxyglucose at the same time as electrical stimulation was delivered through the attack electrodes. Brains prepared for X‐ray autoradiography revealed that lateral hypothalamic stimulation activated the classical medial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

1981
1981
1991
1991

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 60 publications
(2 citation statements)
references
References 14 publications
1
1
0
Order By: Relevance
“…Concerning the statement that a "stimulus-bound" appetitive behavior does not change when an electrode is passed through the relevant hypothalamic field in a given cat, we have observed that the region from which quiet biting attack can be obtained is quite limited (approximately 0.5-1.0 mm. across), and that this observation supports the specificity hypothesis (Fuchs, Dalsass, Siegel, & Siegel 1981). In addition, in studies dealing with affective display behavior, we have routinely found that dorsomedial hypothalamic stimulation will evoke flight behavior and that, as the electrode is passed ventrally for a short distance into the region of the ventromedial nucleus, the behavior evoked changes to affective display.…”
Section: Allan Siegelsupporting
confidence: 71%
“…Concerning the statement that a "stimulus-bound" appetitive behavior does not change when an electrode is passed through the relevant hypothalamic field in a given cat, we have observed that the region from which quiet biting attack can be obtained is quite limited (approximately 0.5-1.0 mm. across), and that this observation supports the specificity hypothesis (Fuchs, Dalsass, Siegel, & Siegel 1981). In addition, in studies dealing with affective display behavior, we have routinely found that dorsomedial hypothalamic stimulation will evoke flight behavior and that, as the electrode is passed ventrally for a short distance into the region of the ventromedial nucleus, the behavior evoked changes to affective display.…”
Section: Allan Siegelsupporting
confidence: 71%
“…A neural projection route that travels between the preoptic region and the VTA, which we have shown to be particularly important for retrieving and nest building, has also been shown to be important for the control of other types of oral motor responses, including (a) angiotensin-induced drinking in rats (Swanson et al, 1978); (b) quiet biting attack in cats (Fuchs, Dalsass, Siegel, & Siegel, 1981;Halliday & Bandler, 1981); (c) gnawing induced by electrical stimulation of the lateral hypothalamus (Roberts, 1980). Also worth pointing out is that VTA lesions disrupt hoarding behavior in rats (Stinus, Gaffori, Simon, & Le Moal, 1978).…”
Section: Discussionmentioning
confidence: 75%